2011
DOI: 10.1128/aem.02322-10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Risk Assessment and Epidemiological Typing of Shiga Toxin-Producing Escherichia coli by Using a Novel PCR Binary Typing System

Abstract: Shiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen that causes diarrheal disease in humans and is of public health concern because of its ability to cause outbreaks and severe disease such as hemorrhagic colitis or hemolytic-uremic syndrome. More than 400 serotypes of STEC have been implicated in outbreaks and sporadic human disease. The aim of this study was to develop a PCR binary typing (P-BIT) system that could be used to aid in risk assessment and epidemiological studies of STEC by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Although these swine STEC strains were recovered from samples of 95 healthy finishing pigs from three cohorts within 18 months in the same geographic area, they were composed of three major pathotypes with 16 different combinations of virulence gene profiles and serotypes. The panel of virulence genes in this study included 69 targets, and our results were in agreement with those of another study suggesting that increasing the number of virulence genes in the panel would increase the resolution of the virulence gene profiling (57). Various virulence gene profiles in swine STEC strains have also been reported elsewhere (38)(39)(40)(41)(42)(58)(59)(60).…”
Section: Discussionsupporting
confidence: 80%
“…Although these swine STEC strains were recovered from samples of 95 healthy finishing pigs from three cohorts within 18 months in the same geographic area, they were composed of three major pathotypes with 16 different combinations of virulence gene profiles and serotypes. The panel of virulence genes in this study included 69 targets, and our results were in agreement with those of another study suggesting that increasing the number of virulence genes in the panel would increase the resolution of the virulence gene profiling (57). Various virulence gene profiles in swine STEC strains have also been reported elsewhere (38)(39)(40)(41)(42)(58)(59)(60).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, VF that play an important role in toxin production and attachment to host cells were highly associated with PT groups I ϩ II or PT group I alone, while other VF were associated with PT group III. Previous studies also reported that the number of VF present in STEC isolates increases the pathogenic potential of STEC and the strong association of certain accessory VF with severe illness and outbreaks (12,17,22,27,33,34,36,44). Interestingly, the accessory virulence gene content of the stx 2f -positive STEC isolates that clustered in a distinct branch with two stx-negative EPEC isolates was lower than the other STEC isolates categorized in PT group II.…”
Section: Discussionmentioning
confidence: 85%
“…Although the disease severity and incidence of STEC are not based solely on the pathogenic potential of the organism but also on host-associated and environmental factors, enough information has accumulated that the presence of virulence factors (VF) carried in addition to the stx genes varies considerably between STEC strains and, therefore, could be used to categorize the potential risk of STEC (5,17,(33)(34)(35)(36). The detection frequency of the stx genes observed in this study (1.8%) was comparable with previous studies performed in The Netherlands (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, EHEC (encoding LEE genes, vt , hlyA ) of serotypes O157:H7, O26:H11, O111:H8, O182:H25, and O84:H2 were identified. Serotypes O157:H7, O26:H11, and O111:H8 are part of the “top 7” priority serotypes most frequently implicated in severe illness ( Karmali et al, 2003 ), while O182:H25 and O84:H2 are emerging EHEC that have been previously isolated from humans ( Friedrich et al, 2002 ; Cookson et al, 2006 ; Brandt et al, 2011 ; Delannoy et al, 2013 ). Interestingly, all serotypes excluding O2:H6, O137:H41, O132:H18, and O157:H7 carried the cfaB gene, which codes for part of the colonization factor CFA/I; colonization factors are important virulence determinants which mediate ETEC adherence.…”
Section: Discussionmentioning
confidence: 99%